2018
DOI: 10.1177/2329496518812451
|View full text |Cite
|
Sign up to set email alerts
|

Improving Homeless Point-In-Time Counts: Uncovering the Marginally Housed

Abstract: This article discusses improvements made to the methodology of the Housing and Urban Development (HUD) point-in-time (PIT) homeless census. HUD’s PIT results are presented to Congress as official data for policy consideration. Yet, PIT methodology focuses on visible street homeless individuals and those in shelters while neglecting the “marginally housed” or less visible homeless who live in automobiles or temporarily stay with friends and extended family. Being a hidden population, the marginally housed has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…This phenomenon is used, among others, to estimate the number of homeless people using the point-in-time method. 22 The winter of 2021, colder than in previous years, should intensify this phenomenon. Meanwhile we have observed a completely opposite relationship.…”
Section: Discussionmentioning
confidence: 98%
“…This phenomenon is used, among others, to estimate the number of homeless people using the point-in-time method. 22 The winter of 2021, colder than in previous years, should intensify this phenomenon. Meanwhile we have observed a completely opposite relationship.…”
Section: Discussionmentioning
confidence: 98%
“…Studies in Los Angeles confirmed that Hispanics were more likely to utilize non-traditional housing arrangements, such as staying with extended friends and family or in abandoned buildings ( Conroy and Heer, 2003 ), and thus are largely undercounted ( Los Angeles County Department of Health Services, 1995 ). Research finds the same large undercounting in El Paso ( Smith and Castaneda, 2019 , 2020 ). Factors including language, citizenship status, social network characteristics, unstable labor arrangements, among others, might affect Hispanics’ choice to utilize non-traditional housing arrangements ( Conroy and Heer, 2003 ; Tan and Ryan, 2001 ).…”
Section: Introductionmentioning
confidence: 86%
“…Data for this study comes from ethno-surveys—which collect close-ended quantifiable data and open-ended answers ( Massey, 1987 )—conducted in El Paso, Texas, USA, in 2011 and 2012. They were conducted face-to-face by the first author, and research teams trained for months as part of a class on research methods ( Smith and Castaneda, 2019 ; Loza et al., 2017 ). The ethno-surveys were conducted in English or Spanish, depending on the preference of the respondent.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This comprises a count on a single night of the people in a community who are experiencing homelessness including both sheltered and visible unsheltered populations (such as rough sleepers). This methodology is common; however, it has been criticised for its focus on visible street homelessness and those living in shelters, while the “marginally housed” such as those staying temporarily with friends or family, and those who experience homelessness intermittently are excluded (Smith & Castaneda‐Tinoco 2018).…”
mentioning
confidence: 99%